Multiscale design and fabrication of neutron shielding composites via boron-based polymers and layer-by-layer assembly of graphene oxide/B₄C on carbon fiber - Yizhuo Gu; Benben Liu; Zhongjia Yang; Shaokai Wang; Min Li (Journal of Materials Research and Technology)
Fiber-reinforced polymer composites (FRP) have multifunctional properties of structural support and radiation shielding, which can meet the lightweight requirements of space exploration. However, the filtering effect of fiber bundles on the functional fillers reduces the shielding properties of the composites. This study enhances neutron shielding properties by developing a B-containing polymer matrix through blending B-phenolic/epoxy with trimethoxyboroxine, followed by the deposition of B₄C/GO multilayers on carbon fibers using a layer-by-layer (LBL) self-assembly method. The microstructures of B₄C/GO layers happening the carbon fibers were characterized using scanning electron microscopy and nanoscale infrared spectroscopy. The assembled fibers and B-containing matrix were then fabricated into laminate composites via hot pressing. The resulting composite, featuring four layers of assembly on the fiber surface, achieves a thermal neutron linear attenuation coefficient (μ) of 2.989 cm⁻1 and a tensile strength of 830 MPa, showing strong structural integrity and effective radiation shielding. Furthermore, Monte Carlo simulations were conducted to research the shielding effectiveness of various filler distribution models, including homogeneous, heterogeneous (fillers accumulating between fiber bundles) and the proposed surface-assembly model. The results indicate that the μ of the surface-assembly model is 9.1% higher than that of heterogeneous model due to reduced neutron penetration zones. Therefore, LBL self-assembly is a promising approach to avoid the degradation of shielding performance caused by the “filtering effect” in FRPs.